Potential use of antibodies to provide an earlier indication of lymphatic filariasis resurgence in post–mass drug ad ministration surveillance in American Samoa - Cadavid Restrepo, Angela M.; Gass, Katherine; Won, Kimberly Y.; Sheel, Meru; Robinson, Keri; Graves, Patricia M.; Fuimaono, Saipale; Lau, Colleen L (International journal of infectious diseases, 2022)
•The patterns of the antibody (Ab) responses varied across the 3 transmission assessment surveys (TASs).•The overall and school-level prevalence of Bm33 Ab was the highest in all TASs.•Bm14 Ab-positive schools decreased, whereas Wb123 Ab-positive schools increased.•Abs could provide earlier signals of resurgence and enable a timelier response.•The role of Abs in post–mass drug administration surveillance should be further investigated. Under the Global Programme to Eliminate Lymphatic Filariasis (LF), American Samoa conducted 7 rounds of mass drug administration (MDA) between 2000 and 2006. The territory passed transmission assessment surveys (TASs) in 2011 (TAS-1) and 2015 (TAS-2). In 2016, the territory failed TAS-3, indicating resurgence. This study aims to determine if antibodies (Abs) may have provided a timelier indication of LF resurgence in American Samoa. We examined school-level antigen (Ag) and Ab status (presence/absence of Ag- and Ab-positive children) and prevalence of single and combined Ab responses to Wb123, Bm14, and Bm33 Ags at each TAS. Pearson chi-square test and logistic regression were used to examine associations between school-level Ab prevalence in TAS-1 and TAS-2 and school-level Ag status in TAS-3. Schools with higher prevalence of Wb123 Ab in TAS-2 had higher odds of being Ag-positive in TAS-3 (odds ratio [OR] 24.5, 95% confidence interval [CI] 1.2–512.7). Schools that were Ab-positive for WB123 plus Bm14, Bm33, or both Bm14 and Bm33 in TAS-2 had higher odds of being Ag-positive in TAS-3 (OR 16.0–24.5). Abs could provide earlier signals of resurgence and enable a timelier response. The promising role of Abs in surveillance after MDA and decision making should be further investigated in other settings.